Coaching school hockey in Malaysia: A exploratory analysis and effect of improvised TGfU pedagogical model on small sided game play - Sanmuga, N. (Journal of Physical Education and Sport, 2015)
This study explored anthropometric, speed and accuracy executing general hockey skills, cardiovascular endurance, leg power and 30 meter sprinting among players. Next, the study investigated the effects of improvised Teaching Games for Understanding (TGfU) model on ball control, decision making and skill execution in 5 vs. 5 small sided game play between high-skilled players (HS) and low skilled-players (LS). A total of n= 30 (age: 14-15 yrs) Malaysian male school field hockey players randomly selected and distributed equally HS and LS group. The findings revealed that the height and weight as well as body structure of mesomorphy of the school players are suitable for nature hockey game. Meanwhile, players performance status in term of speed and accuracy in executing general hockey skills were above average level. However, poor results indicated in term of VO2max, leg power, and sprinting 30 meters. On the other hand, quasi experimental findings indicated no significant difference in term of ball control, decision making and skill execution in 5 vs. 5 game play between HS and LS after intervention, however both group improve from pre-test to post-test in term of mean score. Future study, reexamining the improvised TGfU model is encouraged.